2013
DOI: 10.1016/j.pain.2013.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected association of the “inhibitory” neuroligin 2 with excitatory PSD95 in neuropathic pain

Abstract: In the spinal nerve ligation (SNL) model of neuropathic pain, synaptic plasticity shifts the excitation/inhibition balance toward excitation in the spinal dorsal horn. We investigated the deregulation of the synaptogenic neuroligin (NL) molecules, whose NL1 and NL2 isoforms are primarily encountered at excitatory and inhibitory synapses, respectively. In the dorsal horn of SNL rats, NL2 was overexpressed whereas NL1 remained unchanged. In control animals, intrathecal injections of small interfering RNA (siRNA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 77 publications
2
16
0
Order By: Relevance
“…Moreover, these investigators also found that nlgn2 knockdown, in their case with shRNA, led to an alleviation of mechanical hypersensitivity brought about by peripheral nerve injury yet caused mechanical hypersensitivity in sham rats. 15 This is strikingly similar to our findings with the nlgn2 interfering peptide, neurolide 2. Interestingly, while the study in rats with peripheral nerve injury found an upregulation of the nlgn2(−) splice variant in the spinal cord, 15 we observed an increase in nlgn2A.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Moreover, these investigators also found that nlgn2 knockdown, in their case with shRNA, led to an alleviation of mechanical hypersensitivity brought about by peripheral nerve injury yet caused mechanical hypersensitivity in sham rats. 15 This is strikingly similar to our findings with the nlgn2 interfering peptide, neurolide 2. Interestingly, while the study in rats with peripheral nerve injury found an upregulation of the nlgn2(−) splice variant in the spinal cord, 15 we observed an increase in nlgn2A.…”
Section: Discussionsupporting
confidence: 90%
“…10 Differential expression of these splice isoforms have also been implicated in neuropathic pain. 15 Therefore, we assessed nlgn2 mRNA levels, including these splice variants, using qPCR on spinal dorsal horn and DRG total RNA extracts. We administered i.t.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations